2006
DOI: 10.1093/cercor/bhj138
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Alterations following 5 Days of Intervention: Dynamic Aspects of Neuroplasticity

Abstract: Activation-dependent brain plasticity in humans on a structural level has been demonstrated in adults after 3 months of training a visio-motor skill. The exact timescale of usage-dependent structural changes, whether days, months, or years, is, however, still debated. A better understanding of the temporal parameters may help elucidate to what extent this type of cortical plasticity contributes to fast adapting cortical processes that may be relevant to learning and effects of treatments. Using voxel-based mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
177
3
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(207 citation statements)
references
References 35 publications
19
177
3
7
Order By: Relevance
“…Our data showed a rapid GM increase in sensorimotor-related brain areas as early as after two training days (2 ϫ 45 min) that were separated by 1 week which, subsequently decreased to the last 4 weeks. A recent study in humans also found macroscopic changes in GM as early as after 5 days of continuous intervention with repetitive transcranial magnetic stimulation (May et al, 2007). Together, these results support the idea of rapid intracortical remodeling of dendritic spines and axonal terminals as a possible biological substrate for GM changes in humans (Trachtenberg et al, 2002; Markham and Greenough, 2004;DeBello, 2008;Butz et al, 2009;Xu et al, 2009).…”
Section: Biological Substrates Of Gray Matter Changessupporting
confidence: 68%
“…Our data showed a rapid GM increase in sensorimotor-related brain areas as early as after two training days (2 ϫ 45 min) that were separated by 1 week which, subsequently decreased to the last 4 weeks. A recent study in humans also found macroscopic changes in GM as early as after 5 days of continuous intervention with repetitive transcranial magnetic stimulation (May et al, 2007). Together, these results support the idea of rapid intracortical remodeling of dendritic spines and axonal terminals as a possible biological substrate for GM changes in humans (Trachtenberg et al, 2002; Markham and Greenough, 2004;DeBello, 2008;Butz et al, 2009;Xu et al, 2009).…”
Section: Biological Substrates Of Gray Matter Changessupporting
confidence: 68%
“…Recent longitudinal morphometry studies demonstrated that repeated practicing of a visuomotor task and intense learning of abstract information could lead to gray matter density changes in task-related regions of brain. 3,7,27 In summary, the results of cross-sectional and longitudinal in vivo morphometric MR imaging studies point to the presence of experience-dependent structural plasticity in the human brain.…”
Section: Discussionmentioning
confidence: 97%
“…Results of recently reported longitudinal studies revealed that experience-dependent structural changes may develop within weeks or months after the stimuli. 7,27 Structural changes observed in left inferior frontal gyrus and left inferior parietal lobule may develop in earlier times of the professional careers of mathematicians. Left inferior frontal gyrus is a language-related region of arithmetic processing.…”
Section: Figmentioning
confidence: 99%
“…However, several studies have shown that regional GM values are directly related to functional abilities (Maguire et al, 2000;Gaser and Schlaug, 2003;Mechelli et al, 2004). Moreover, an increase in GM can be induced by training and activation, which has been demonstrated for training of juggling for 3 months (Draganski et al, 2004), intensive studying for 3 months (Draganski et al, 2006), and repetitive transcranial magnetic stimulation (rTMS) for only 5 d (May et al, 2007). The relationship of induced GM changes and cerebral activation has not been investigated.…”
Section: Introductionmentioning
confidence: 99%